2006
DOI: 10.1021/jp061451u
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polymer Molecular Weight on the Chemical Modifications Induced by UV Laser Ablation

Abstract: This paper investigates the influence of polymer molecular weight (M(W)) on the chemical modifications of poly(methyl methacrylate), PMMA, and polystyrene, PS, films doped with iodonaphthalene (NapI) and iodophenanthrene (PhenI), following irradiation at 248 nm (KrF excimer laser, 20 ns fwhm and hybrid excimer-dye laser, 500 fs fwhm) and at 308 nm (XeCl excimer laser, 30 ns fwhm). The changes of intensity and position of the polymer Raman bands upon irradiation provide information on cleavage of the polymer bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 47 publications
2
37
0
Order By: Relevance
“…[1][2][3] This process is commonly observed in large molecules, particularly in polymers during their service lifetime. The long molecular chain of polymer makes the material susceptible to degradation and the level of deteriorations shows linear dependence to the polymers molecular weight, as reported by Rebollar et al 4 The strength of reacting ultra-violet (UV) photons (e.g. UVA, UVB, UVC etc.)…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…[1][2][3] This process is commonly observed in large molecules, particularly in polymers during their service lifetime. The long molecular chain of polymer makes the material susceptible to degradation and the level of deteriorations shows linear dependence to the polymers molecular weight, as reported by Rebollar et al 4 The strength of reacting ultra-violet (UV) photons (e.g. UVA, UVB, UVC etc.)…”
Section: Introductionmentioning
confidence: 84%
“…The degradation is more pronounced if cleavage happens at the main chain as compared to side chain scission as this may lead to photo-ablation. 4 In order to suppress the polymer sensitivity towards light, UV-inhibitors from the classes of benzotriazoles (e.g. 2-(2 0 -hydroxyphenyl) benzotriazoles), metallic complexes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This value of critical bond break fraction is specific to the MD-polymer model used here, which has relatively short polymer chains ͑19 MMA units͒. Recent experimental studies 57,58 have shown that shorter chains have lower levels of entanglement, requiring fewer bonds to be broken for an efficient removal of monomers and polymer fragments by ejection. Longer chains with higher molecular weight will require a higher degree of decompo- sition to achieve ablation.…”
Section: Ejection Mechanismsmentioning
confidence: 95%
“…We can see the broad emission shoulder with a narrow peak at 630nm. It is feasible that the fluorescence was caused by some kind of functional group, such as a kind of cyclic compound, resulting from the UV laser ablation [13,14], but it cannot be identified from the narrow spectral area only.…”
Section: Autofluorescence From Uv Laser-grooved Pmma Substrate With Amentioning
confidence: 99%